A teleost TFPI-2 peptide that possesses a broad antibacterial spectrum and immune-stimulatory properties. Issue 82 (November 2018) - He, Shu-wen; Wang, Jing-jing; Du, Xue; Yue, Bin; Wang, Guang-hua; Zhou, Shun; Xie, Bing; Zhang, Min
Abstract: Tissue factor pathway inhibitor 2 (TFPI-2) is an analogue of TFPI-1 and a potent endogenous inhibitor of tissue factor (TF)-mediated blood coagulation. Previous reports have shown that several peptides derived from human and vertebrates TFPI-2 possess antibacterial activity against diverse bacteria. In this study, a C-terminal peptide, TO24 (with 24 amino acids), derived from red drum ( Sciaenops ocellatus ) TFPI-2, was synthesized and investigated for its antimicrobial spectrum, action mode, as well as the immune-stimulatory property. Our results indicated that TO24 was active against Gram-positive bacteria Micrococcus luteus and Staphylococcus aureus ; Gram-negative bacteria Vibrio litoralis, Vibrio ichthyoenteri, Vibrio vulnificus and Vibrio scophthalmi, as well as fish megalocytivirus, infectious spleen and kidney necrosis virus (ISKNV). During its interaction with V. vulnificus, TO24 exerted its antibacterial activity by destroying cell membrane integrity, penetrating the cytoplasm and inducing degradation of genomic DNA and total RNA. In addition, TO24 had no hemolytic activity against red drum blood cells. In vitro, TO24 enhanced bactericidal activity of red drum macrophages. In vivo, administration of red drum with TO24 before bacterial infection significantly reduced pathogen dissemination and replication in tissues. These results indicate that TO24 is a broad-spectrum antimicrobial peptide with immune-stimulatory properties and it has the potential to be used as an antimicrobial agent in aquaculture. Highlights: A red drum TFPI-2 peptide TO24 was bactericidal against Gram-positive and Gram-negtive bacteria. TO24 displayed antiviral activity against infectious spleen and kidney necrosis virus. TO24 destroyed cell membrane integrity, penetrated into the cytoplasm, and induced degradation of nucleic acids. TO24 enhanced the bactericidal activity of red drum macrophages. TO24 could inhibit bacterial invasion in red drum.